Peningkatan Pengetahuan KESGILUT pada Anak Berkebutuhan Khusus melalui Aplikasi Teledentistry - Valendriyani Ningrum; Abu Bakar (Universitas Lancang Kuning, 2021)
The parents of special needs children (SNC) problem in West Sumatra is the poor oral health of SNC, due to a lack of oral and dental health maintenance knowledge. The teledentistry application “SpecialSmile” is the solution offered. The aim is to improve oral health knowledge remotely. The method is carried out by preparing educational content in scientific articles or audiovisuals form. Program evaluation was collected by filling out a questionnaire containing 10 questions about oral health knowledge, before and after using this application. Data analysis was done descriptively. The results obtained from 49 users, before using the application only 22.95% of parents had good knowledge and after using the application there was an increase of 80.33% of parents who had good knowledge regarding oral health maintenance among SNC. This program concludes that remote education using the SpecialSmile application can increase the knowledge of ABK parents about maintaining SNC's oral health